Evaluation of culture conditions for the vegetative growth of different strains of Lentinula edodes (Berk.) Pegler - Lata, Hem; Sharma, S R (Mushroom Research, 2012)
Studies has been carried out to find the most suitable media, temperature, pH, growth regulator and trace element for the vegetative growth of five strains of Lentinula edodes. Out of 13 solid media evaluated, malt extract agar medium supported the maximum radial growth of all the five strains followed by potato dextrose agar medium. Among 17 broth culture, maximum mycelial dry weight was recorded in Asthana and Hawker’s media for all the five strains. Other promising broth cultures were malt extract peptone dextrose and Walksman’s broth. Optimum temperature for the growth of all the strains was 20°C and 25°C. With further increase or decrease in temperature there was corresponding decrease in the mycelial growth. Most suitable pH for the growth of strains OE-17, OE-38, OE-142, OE329 and OE-388 were 7.5, 6.0, 7.5, 7.5 and 5.5-9.5, respectively. Out of four different growth regulators tried, Kinetin at 10 ppm concentration supported the maximum mycelial growth of all the five strains while among the four trace elements tried, the strains OE-17 and OE388 showed maximum growth at 10 ppm of ammonium molybedate; whereas strains OE38, OE-142 and OE-329 showed maximum growth at 5 ppm of ammonium molybedate, 10 ppm of Zinc sulphate and 20 ppm of MnCl 2, respectively.